LncRNA Mirt2 Is Downregulated in Ulcerative Colitis and Regulates IL-22 Expression and Apoptosis in Colonic Epithelial Cells. (7th October 2019) - Ding, Guangrong; Ming, Yuzheng; Zhang, Yuling
Abstract : lncRNA Mirt2 is a lipopolysaccharide- (LPS-) inducible inflammation inhibitor. We found that Mirt2 was downregulated in plasma of ulcerative colitis (UC) patients and the downregulation of Mirt2 distinguished UC patients from healthy controls. IL-22 was also downregulated in UC patients and positively correlated with Mirt2. Mirt2 overexpression led to upregulated, while Mirt2 siRNA silencing led to inhibited secretion of IL-22 from colonic epithelial cells treated with LPS. In addition, under LPS treatment, Mirt2 overexpression led to decreased, while Mirt2 siRNA silencing led to increased apoptotic rate of colonic epithelial cells. Therefore, Mirt2 is downregulated in ulcerative colitis and regulates IL-22 expression in colonic epithelial cells.